Pertanggungjawaban Pidana Mitra Pengemudi Ojek Online atas Tindak Pelecehan Seksual Perspektif UU No. 12 Tahun 2022 - Muhammad Sulton Alrasyid; H. R. Adianto Mardijono (STIH Zainul Hasan Kraksaan Kraksaan, 2026)
Sexual harassment itself can be defined as the occurrence of unwanted sexual approaches by someone against another person, sexual harassment can also be in the form of non-physical actions, such as whistling, body language that shows also playing genitals, speech that leads to sexuality, invitations to have sex, showing pornographic videos, and secretly recording or photographing the victim's body and spying on someone. The formulation of the problem to be discussed in this study is how the criminal liability of online motorcycle taxi driver partners who commit sexual harassment to cutomers. This research uses normative law. The criminal liability of online motorcycle taxi drivers who commit sexual harassment to customers is as follows: 1) If the act of sexual harassment is non-physical sexual harassment, it will be subject to criminal liability in accordance with Article 5 of Law Number 12 of 2022 concerning Criminal Sexual Violence, namely imprisonment for a maximum of 9 (nine) months and / or a maximum fine of Rp. 10,000,000.00 (ten million rupiah). 2) If the act of sexual harassment is physical sexual harassment, it will be subject to sanctions in accordance with Article 6 of Law No. 12 of 2022 concerning Criminal Acts of Sexual Violence in the form of imprisonment of 4 (four) years or more and a fine. 3) In addition to being sentenced, perpetrators of sexual violence can be subject to rehabilitation in accordance with Article 17 of Law No. 12 of 2022 concerning Criminal Acts of Sexual Violence, namely medical rehabilitation and social rehabilitation.